The relationship between work-life balance and job performance in manufacture sports apparel at Ramatex Textiles Industrial / Shahrir Fitri Shahrulzaman and Mohammad Adzly Rajli - Shahrulzaman, Shahrir Fitri; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Work-life balance plays a crucial role in employee well-being and overall organizational success. In Malaysia, work-related challenges have become increasingly evident, affecting both productivity and job satisfaction. Malaysia has one of the highest voluntary turnover rates in Southeast Asia, with 6.0% and the third highest voluntary turnover rate of 9.5% in Southeast Asia [1]. Additionally, Malaysia ranks as the second worst for work-life balance due to long working hours, low wages, and minimal statutory leave, leading to a decline in employee well-being and job satisfaction [2]. This poor work-life balance further contributes to anxiety, depression, burnout, and reduced productivity, ultimately harming both individual well-being and overall organizational performance. Addressing these issues is crucial for developing a more sustainable and productive workforce [3].